2016
DOI: 10.12962/j24433527.v9i2.1623
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Persepsi Melalui Pelibatan Masyarakat Dalam Proses Analisis Mengenai Dampak Lingkungan (Amdal) Pltgu Perak

Abstract: The residential area and industrial economy in Indonesia specifically East Java has grown rapidly. This is a challenge for National Electricity Board such as P.T. PLN Persero East Java to supply the energy sufficiently. Therefore P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Furthermore, Thoha states that perception is a unique interpretation of a situation and not an actual record of that situation. Thus, the public's perceptions and attitudes toward the project plan in the EIA may not be in accordance with the actual facts as found by Susilowati and Moerad (2016), who found that a development plan that benefits the people will usually experience obstacles from the public in the form of a negative perception of the plan. Thoha's definition of perception does not mention that information and situations can serve as stimuli for the formation of a perception.…”
Section: Theories Of Perceptions and Attitudes And The Legal Basis Fo...mentioning
confidence: 84%
“…Furthermore, Thoha states that perception is a unique interpretation of a situation and not an actual record of that situation. Thus, the public's perceptions and attitudes toward the project plan in the EIA may not be in accordance with the actual facts as found by Susilowati and Moerad (2016), who found that a development plan that benefits the people will usually experience obstacles from the public in the form of a negative perception of the plan. Thoha's definition of perception does not mention that information and situations can serve as stimuli for the formation of a perception.…”
Section: Theories Of Perceptions and Attitudes And The Legal Basis Fo...mentioning
confidence: 84%
“…Adanya proyek pembangunan pembangkit listrik tersebut maka akan memberikan dampak yang baik bagi masyarakat, baik dalam segi ekonomi, sosial atau pun budaya (Prastiwi, Soesilowati, and Setyowati 2016). Pembangunan selain akan menimbulkan dampak positif, juga dapat berdampak negatif berupa terjadinya perubahan lingkungan atau terjadi pencemaran dan kerusakan lingkungan (Susilowati and Moerad 2016).…”
Section: Pendahuluanunclassified
“…Oleh sebab itu, AMDAL adalah singkatan dari Analisis Mengenai Dampak Lingkungan. Sedangkan UKL-UPL dalam (Susilowati & Moerad, 2016) adalah sebuah perizinan daerah yang disusun bersamaan dengan studi kelayakan rencana usaha/kegiatan, sehingga layak secara teknis, ekonomi dan lingkungan. Pada hakikatnya, UKL-UPL adalah singkatan dari Upaya Pengelolaan Lingkungan Hidup dan Upaya Pemantauan Lingkungan Hidup.…”
Section: B Metode Penelitianunclassified